Comparing Prognostic Tools for Cancer Screening: Considerations for Clinical Practice and Performance Assessment. Issue 5 (30th April 2016) - Pollack, Craig Evan; Blackford, Amanda L.; Schoenborn, Nancy L.; Boyd, Cynthia M.; Peairs, Kimberly S.; DuGoff, Eva H.
Abstract : Objectives: To compare the agreement and rates of cancer screening using four prognostic tools that require different types of clinical information. Design: Observational retrospective cohort study. Setting: 2009 and 2010 waves of the Medicare Current Beneficiary Survey. Participants: Adults aged 66–90 with survey and claims data ( N = 9, 469). Measurements: Agreement between four indices predicting short‐term (4–5 years) and long‐term (9–10 years) survival; self‐reported breast and prostate cancer screening. Results: Agreement between the four prognostic tools was high. Pearson correlation coefficients ranged from 0.63 to 0.90 for short‐term survival and 0.68 to 0.94 for long‐term survival. When defining limited short‐term life expectancy as less than 25% chance of surviving 4 or 5 years, all four tools agreed in 96.4% of the sample. All four tools agreed in their placement of participants into limited or not‐limited long‐term life expectancy in 77.1% of participants (<25% chance of surviving 9 or 10 years). Rates of cancer screening were similarly high in individuals with limited long‐term life expectancy regardless of the tool used: greater than 31% for mammographic screening in women and greater than 69% for prostate cancer screening. Conclusion: There is substantial agreement among different prognostic tools for short‐ and long‐term survival in Medicare beneficiaries. The high rates of cancer screening of individuals with limited life expectancy suggest the importance of incorporating tools into clinical decision‐making.